ANALYSIS OF MSME ENTREPRENEURSHIP (CASE STUDY ON MSME KINO’S CHICKEN) IN GOWA REGENCY - AYU HASRA NURFAIZA; MUHAMMAD JUFRI, AGUS SYAM, NUR HALIM, ANDIKA ISMA (Jurnal Ekonomi dan Bisnis, 2026)
This research aims to analyze the application of entrepreneurial aspects, including innovation, creativity, and resource management, in enhancing competitiveness and the development of Kino’s Chicken SMEs in Gowa Regency. The research uses a descriptive qualitative case study approach, with data collected through interviews, observations, and documentation. The research results show that Kino’s Chicken implements product and service innovations, such as menu variant development and the use of digital platforms (GoFood and GrabFood), to create market differentiation. Creative marketing strategies, including seasonal promotions and storytelling on social media, have successfully expanded the customer reach. Resource management is carried out efficiently through task division based on expertise, daily procurement of raw materials, and disciplined financial record-keeping. Supporting factors include sensitivity to the market and digital technology, while challenges include limited human resources and competition with large-capital businesses. The research conclusion states that innovation, creativity, and adaptive resource management are key to the sustainability and growth of SMEs like Kino’s Chicken. Recommendations include product variant development, improvement of social media management, and seeking stable supplier partners